Monitoring Global Poverty : Report of the Commission on Global Poverty - World Bank (Washington, DC: World Bank, 2016)
In 2013, the World Bank Group announced two goals that would guide its operations worldwide. The first is the eradication of chronic extreme poverty -- bringing the number of extremely poor people, defined as those living on less than 1.25 ppp-adjusted dollars a day, to less than 3% of the world population by 2030. The second is the boosting of shared prosperity, defined as promoting the growth of per capita real income of the poorest 40% of the population in each country.